Management of Business Processes with the BPRules Language in Service Oriented Computing - Comes, Diana; Bleul, Steffen; Zapf, Michael (Electronic Communications of the EASST, 2009)
Quality of Service (QoS) concerns are an important topic for the realization of business processes. While BPEL is considered the de facto standard for web service compositions, QoS requirements are not part of its specification. We present the BPRules (Business Process Rules) language for the management of business processes with respect to QoS concerns. BPRules is a rule-based, declarative language which brings novel benefits in the management of business processes, like QoS dependability for sub-orchestrations and corrective actions tailored to the specific needs of the clients. We present the main constructs of the BPRules language and how they support the flexible adaptation of the business process during runtime. Decision making is done according to the behavior of several process executions. An illustrative scenario shows how BPRules is applied to a business process.